PROFIL MENTAL ATLET PEKAN OLAHRAGA PROVINSI (PORPROV) VII PETANQUE SUMENEP DILIHAT DARI PERSPEKTIF IMAGERY DAN SELF TALK - Holifatul Jennah; Choli Astutik; Nur Fitriyah Indraswari; Feri Weldani (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The purpose of this study was to determine the Mental Athletes of PORPROV (one of the prestigiouns sporting event in East Java) VII East Java Petanque Sumenep Seen from the Perspective of Imagery and Self Talk. The method used in this study is descriptive qualitative method, subject in the research is athlete of Sumenep petanque sport who participated in the PORPROV championship in 2022 as many as 9 athletes, the instruments used were observation and questionnaires. The results of the study were obtained using an image questionnaire and self talk to determine the mentality of Sumenep's petanque athletes at the PORPROV event. The value from the perspective of imgeri, the mental imagery of PORPROV petanque Sumenep athletes is categorized as moderate with a percentage of 67%. Meanwhile, from the perspective of self talk, PORPROV petanque Sumenep athletes in the use of self talk or talking to themselves are categorized as high with a percentage of 45%. The conclusion is to use imagery and self talk for Sumenep petanque athletes who take part in the PORPROV athlete championship in 2022 can help athletes overcome poor mentality so that they can overcome fear and be able to complete the match optimally.